Active ageing Voluntary work by older people in Europe - Lamura, Giovanni; Jensen, Per H.; Principi, Andrea (Policy Press, 2014)
In this topical book older people's volunteering is studied in eight European countries at the structural, macro, meso and micro levels. Overall it highlights how different interactions between the levels facilitate or hinder older people's inclusion in voluntary work and makes policy suggestions for an integrated strategy.
Description based on print version record.
KU Select 2018: HSS Backlist Books
Keywords: Social Science / Sociology; Social sciences; Electronic books